Seasonal changes in ammonium regeneration and potential uptake rates in boreal lake Jyväsjärvi - Heinonen, Miina (2023)
Boreal lakes experience fluctuations between ice cover and ice-off periods every year. The duration of ice cover plays a crucial role in understanding nitrogen cycling in these lakes. During the brief growing season, lakes experience rapid changes, in nitrogen cycle particularly during spring. Our current understanding of nitrogen cycling in lakes is limited to redox-driven chemical reactions in shallow, eutrophic lakes during ice free periods or in arctic unproductive lakes, rarely considering seasonal changes. The aim of this study was to investigate temporal changes in ammonium (NH4+) regeneration and potential uptake rates from ice cover period to the late autumn using stable isotope (15NH4+) enrichments and isotope dilution models. Water column NH4+ cycling data was collected from a small, humic lake in central Finland (Jyväsjärvi) during 2023 from the areas near a small river discharge and the central part of the western basin. Potential NH4+ uptake rates followed seasonal patterns and were higher close to a nutrient source (tributary input) and near the sediments compared to surface waters. Ammonium regeneration within the water column supported a larger proportion of community NH4+ uptake during low light conditions and colder temperatures. Ammonium regeneration rates in Jyväsjärvi were mainly affected by temperature, light, and availability of nutrients. Photoautotrophic production was observed under the ice, showing that some light penetrated the snow and ice layers. Further studies are required to understand the contributions of humic substances and bacterial activities in boreal lakes to overall nitrogen cycling dynamics during the winter period.